Immobilization of bioactive factor-loaded liposomes at the surface of electrospun nanofibers targeting tissue engineering strategies - Monteiro, Nelson (2013)
Publicado em "Journal of Tissue Engineering and Regenerative Medicine", vol. 7, supp. 1 (2013)